Functional outcome of displaced tibial plateau fracture treated by Illizarov fixator - Jayabalan, Surulivel Vignesh; Ram, Ganesan Ganesan; Chandrasekaran, Annamalai; Kailash, Kannan Karthik (International Journal of Advances in Medicine, 2017)
Background: The tibial plateau fracture is a typical example of complex periarticular trauma, which has been and continues to be a considerable clinical challenge to the orthopaedician in terms of decision-making in management. Residual functional deficits in case of complex knee trauma treated with open reduction and internal fixation even when delayed till recovery of soft tissues were found to be significant. With this knowledge, we proposed to conduct a study on the effectiveness of the Illizarov technique in management of displaced tibial plateau fractures. Methods: Prospective study of twenty two cases of complex tibial plateau fracture treated with Illizarov fixator done in Sri Ramachandra medical centre between June 2011-June 2013. The inclusion criteria were closed Schatzker type V & type VI tibial plateau fracture. The exclusion criteria were Schatzker Type I, II, III and IV tibial plateau fracture and any other associated lower limb fractures. The post op outcome was measured using the knee society score at each follow up and the final scoring was done at the final follow up. Results: The average knee society knee score was 78.09 and the average function score was 93.5. We had 95% of excellent/good result. Conclusions: Illizarov technique gives good to excellent results in high energy closed and open tibial condylar fractures. The Illizarov method offers significant advantage in the case of fracture blisters with impending compartment syndrome associated with closed high energy tibial plateau fractures. Illizarov technique provides the greatest advantage of ability to maintain the functional status of the extremity.